Performance of intervarietal crosses of maize and sweet corn and correlations among agronomic characters - Tan, Swee Lian; Yap, Thoo Chai (Faculty of Agriculture, University of Malaya, 1973)
Four open-pollinated varieties of maize and sweet corn, Guatemala, Chinta, Hawaiian Sugar and Hawaiian Supersweet 4 were crossed in all possible combinations and evaluated in the field in 1972. Among the 13 characters studied, days to flowering, Helminthosporium score, plant height, ear height, ear length, ear diameter, number of kernel rows per ear, shelling percentage, 100-kernel weight and number of kernels per ear were significantly correlated to grain yield per plot. Helminthosporiu n score was negatively correlated with most of the characters. Of the seven crosses that yielded better than Chinta five involved Guatemala as one of their parents. Since Guatemala is a high yielding starchy maize the incorporation of the high yield characteristics of this variety into sweet corn varieties may be one way to improve local sweet corn.